2022
DOI: 10.1016/j.ejca.2021.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Impaired seroconversion after SARS-CoV-2 mRNA vaccines in patients with solid tumours receiving anticancer treatment

Abstract: Background Patients with solid tumours have high COVID-19 mortality. Limited and heterogeneous data are available regarding the immunogenicity of SARS-CoV-2 mRNA vaccines in this population. Methods and Findings This is a prospective, single-center, cohort study aiming at evaluating seroconversion in terms of anti-spike antibodies in a population of patients with solid tumours undergoing cancer therapy within 2 months before the second vaccine dose, as compared with a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 40 publications
4
25
0
Order By: Relevance
“…Patients with cancer are at a significantly increased risk of severe morbidity and mortality from coronavirus disease of 2019 (COVID-19) [ [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] ]. In a previous report, we showed that an adequate antibody response was achieved after two doses of BNT162b2, but not after one, in patients with cancer vaccinated during anticancer therapy, and at lower seropositivity rates compared with healthy controls [ 10 ], in accordance with additional reports [ [11] , [12] , [13] , [14] , [15] ]. Conflicting data came from follow-up studies showing that seropositivity rates among patients with cancer compared with healthy controls were lower at four months after the second vaccine dose [ 16 ], but were similar at six months [ 17 ].…”
Section: Introductionsupporting
confidence: 90%
“…Patients with cancer are at a significantly increased risk of severe morbidity and mortality from coronavirus disease of 2019 (COVID-19) [ [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] ]. In a previous report, we showed that an adequate antibody response was achieved after two doses of BNT162b2, but not after one, in patients with cancer vaccinated during anticancer therapy, and at lower seropositivity rates compared with healthy controls [ 10 ], in accordance with additional reports [ [11] , [12] , [13] , [14] , [15] ]. Conflicting data came from follow-up studies showing that seropositivity rates among patients with cancer compared with healthy controls were lower at four months after the second vaccine dose [ 16 ], but were similar at six months [ 17 ].…”
Section: Introductionsupporting
confidence: 90%
“…This additional information may provide a more accurate indication about the efficacy of protection 31 . Indeed, in a prospective, single-center cohort study up to 6% of patients with solid tumors undergoing cancer treatment, mainly with poorer performance status, fail to obtain seroconversion after primary SARS-CoV-2 mRNA vaccination as compared with 0.2% of controls without cancer, accounting for a 30-fold higher probability 32 . After the third dose an additional, although incomplete, efficacy of vaccination in this population was reported, with an estimate of 35.7% of seroconversion probability 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Further, such data are consistent with another recently published report in a mixed onco-hematologic population, showing 56% seroconversion 4. In conclusion, even though a variable percentage of patients with solid tumors display immunization after booster despite seronegativity after previous primary vaccine, there is a subpopulation who persistently fails to achieve seroconversion (roughly one third of those who remained seronegative after primary vaccination) 1 , 3 , 4 . This finding is concerning, as boosters are the leading strategy to enhance immunization.…”
Section: Correspondencementioning
confidence: 95%
“…In the SINFONIA-V study published in the December 2021 edition of the European Journal of Cancer, we sowed that a 5.8% fraction of patients with solid tumors undergoing anticancer treatment do not achieve seroconversion after primary (2 doses) SARS-CoV-2 mRNA vaccination with BNT162b2 or mRNA-1273 (10/171 individuals); this was significantly different as compared with 0.2% of controls without cancer (p <0.001) 1 , 2 . We report here updated data with the analysis of post-booster serological status in these patients (n=10), Interestingly, we found that among 6 evaluable individuals with pre-boosting confirmed seronegativity, 2 (33%) developed anti-spike antibodies after boosting, whereas the remaining showed persistent seronegative status ( Table 1 ).…”
Section: Correspondencementioning
confidence: 96%